PANDANGAN ISLAM MENGENAI STEREOTIP PEREMPUAN DALAM DUNIA POLITIK - amira nurifkah m; M. Abdul Somad; Nurti Budiyanti (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
Women in politics are not easy because of the dominant culture of the patriarchy, so that communication sometimes becomes an obstacle. Islam is a religion that really respects and respects women and men before Allah absolutely. Islam eliminates the Jahiliyah tradition which is so discriminatory against women, in Islam men and women are considered as creatures of Allah who are equal, free to have tasarruf, even mutually complementary and in need of one another. This research is a study that deals with the Islamic view of stereotypes of women in the world of politics. This study uses a descriptive qualitative approach, with the method of collecting literature data, which aims to provide an understanding of how the Islamic religious views regarding stereotypes of women in the political world. The results of this study indicate that women's opportunities for politics are wide open, however, there are several obstacles faced by women in politics, including: gender disagreement and women's subordination in politics, patriarchal political culture, individual barriers, and institutional and structural obstacles. . Ignoring women and not involving them in activities that benefit society means wasting at least half of society's potential. Keyword: Women, Stereotypes, Islam, Politics